Study Ethnobotany of Minyak Karo - Jamilah Nasution; Agung Suharyanto; Eva Sartika Dasopang (Budapest International Research and Critics University, 2020)
Research on the study of Minyak Karo ethnobotany aims to determine the types of plants that are the raw material for making Minyak Karo and its utilization. The method used in the study is a qualitative descriptive method with data collection techniques carried out through an emic approach and an ethical approach to the interview method with producers of Minyak Karo. The results obtained in this study are 42 species from 24 families which are used as ingredients in the production of Minyak Karo. Zingiberaceae is the type most widely used in these herbs. Plant parts used are leaves (16 species), rhizomes (7 species), roots (6 species), seeds (5 species), fruit (4 species), flowers and tubers (2 species each), and stems (1 species). Benefits of Minyak Karo treat aches, treat colds, reduce heat / fever, heal wounds, dry out and treat sunburn, treat itching, strengthen bones in infants, treat lumbago, treat rheumatism, treat sprains, treat body aches, and treat muscle cramps. Minyak Karo is an external medicine so that its use is enough by way of being rubbed, applied or massaged.